Global Trend to Railway Concessions Delivering Positive Results - Thompson, Louis S.; Budin, Karim-Jacques (World Bank, Washington, DC, 2012)
The authors review a number of recent innovative rail concessions. Each country has approached its problems differently, and each provides different insights into what can be achieved with concessions. But all the cases show that restructuring and substantial government investment in the design of a concession pay off. Concessionaires can do exactly what is expected-increase traffic, improve service, and enhance labor and asset efficiency if they are allowed to do so. A growing number of companies and consortiums are interested in investing in railway concessions if the concessions are offered on reasonable terms. And because both "positive" (where the concessionaire pays the government an agreed sum for the concession rights) and "negative" (where the government pays the concessionaire to operate and maintain the property) concessions are possible, loss-making but socially necessary services can also be concessioned. Perhaps the most important innovation in railway organization over the next few decades will be in the European Union. Regulatory changes have ignited a clear trend in the EU toward institutional separation of infrastructure from operations because infrastructure is seen as a state responsibility while operations (except for social services) are seen as commercial. One eventual result of institutional separation will be franchising or even privatization of most freight services and possibly intercity passenger services.